The variable palatal lateral in Occitan and Catalan: linguistic transfer or regular sound change?. Issue 2 (July 2019) - Mooney, Damien; Hawkey, James
ABSTRACT: Occitan and Catalan are in an increasing state of language obsolescence in France. Their phonologies both contain a voiced palatal lateral approximant /ʎ/, not present in modern French, that is being replaced in all positions by the palatal approximant [j]. It is not clear whether this is an effect of language contact with French because [j] commonly emerges as a variant of /ʎ/ in non-contact varieties of Romance. This article examines the distribution of /ʎ/ in Occitan and Catalan, using auditory and acoustic data from a wordlist-translation task conducted with 40 native speakers. The analysis aims to determine the nature of this sound change either as the result of transfer from French or as a regular sound change that is motivated by the phonetic similarity of [ʎ] and [j]. The mechanisms governing transfer from French are modelled statistically to account for the distribution of historically appropriate and contact-induced variants of /ʎ/, and acoustic analyses test the hypothesis that the change is internally motivated and occurring gradually. Results show that the factors conditioning the change may be different in each of these related languages in that it is contact-induced in Occitan, but potentially due to internal and external factors in Catalan.